Cost Efficiency of Restoration of Strepleniya Grids in Agricultural Machinery - Mominovich, Mirzaakhmedov Mirzarakhmat (American Journal of Biodiversity, 2025)
Agricultural machinery and their economic importance. In agriculture, the technique automates and intensifies production processes, which contributes to increasing labor productivity, reducing production costs and improving the quality of products. Agricultural machinery and autotractors and other agricultural machinery are necessary for the productive production process.